2011
DOI: 10.1093/cercor/bhr201
|View full text |Cite
|
Sign up to set email alerts
|

Remote Effects of Hippocampal Sclerosis on Effective Connectivity during Working Memory Encoding: A Case of Connectional Diaschisis?

Abstract: Accumulating evidence suggests a role for the medial temporal lobe (MTL) in working memory (WM). However, little is known concerning its functional interactions with other cortical regions in the distributed neural network subserving WM. To reveal these, we availed of subjects with MTL damage and characterized changes in effective connectivity while subjects engaged in WM task. Specifically, we compared dynamic causal models, extracted from magnetoencephalographic recordings during verbal WM encoding, in tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 114 publications
5
50
0
1
Order By: Relevance
“…Of interest, this pattern took place in a context of mild semantic dysfunction that was evident in different types and modalities of semantic tasks, thus supporting the critical role of the left temporal pole for conceptual knowledge (Bruffaerts et al 2013;Clarke et al 2011Clarke et al , 2013Chan et al 2011;Mesulam et al 2013;Peelen and Caramazza 2012). It is important to highlight that, although current results demonstrate that unilateral damage to the left temporal pole can produce a significant semantic impairment, it is, however, far from the devastating degradation observed in semantic dementia and other bilateral conditions (Antonucci et al 2008;Lambon Ralph et al 2010a, 2012Lambon Ralph et al 2012;Schapiro et al 2013;Tsapkini et al 2011). PC was supported by a Ramon y Cajal Fellowship from the Spanish Ministry of Science and Innovation (RYC-2010-05748). CP was supported by Spanish Ministry of Science and Education (AP2009-4131).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Of interest, this pattern took place in a context of mild semantic dysfunction that was evident in different types and modalities of semantic tasks, thus supporting the critical role of the left temporal pole for conceptual knowledge (Bruffaerts et al 2013;Clarke et al 2011Clarke et al , 2013Chan et al 2011;Mesulam et al 2013;Peelen and Caramazza 2012). It is important to highlight that, although current results demonstrate that unilateral damage to the left temporal pole can produce a significant semantic impairment, it is, however, far from the devastating degradation observed in semantic dementia and other bilateral conditions (Antonucci et al 2008;Lambon Ralph et al 2010a, 2012Lambon Ralph et al 2012;Schapiro et al 2013;Tsapkini et al 2011). PC was supported by a Ramon y Cajal Fellowship from the Spanish Ministry of Science and Innovation (RYC-2010-05748). CP was supported by Spanish Ministry of Science and Education (AP2009-4131).…”
Section: Discussionsupporting
confidence: 69%
“…This is not to say that the temporal pole is the only region involved (Binney et al 2012b). Instead, impaired performance may not be caused solely by local dysfunction of the damaged ATL, or by the disruption that the epileptogenic activity can cause in other brain areas, but by the local and remote changes in the interactions among regions that constitute the network (Campo et al 2012;Carrera and Tononi 2014). Specifically, alteration of the structural and/or functional connectivity from the temporal pole to a speech production mechanism via uncinate fasciculus (Acosta-Cabronero et al 2011;Agosta et al 2010;Blaizot et al 2010;Dick and Tremblay 2012;Han et al 2013;Lambon Ralph 2014;Pascual et al 2014), and from posterior temporal regions via inferior longitudinal fasciculus (Behrmann and Plaut 2013;Campo et al 2013;Clarke et al 2011;Fan et al 2014;Guo et al 2013) could be the mechanism underlying the observed pattern of impairment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are two Bayesian model selection (BMS) approaches for selecting the best (optimal) model at the group-level: fixed-effect analysis (FFX) and random-effect analysis (RFX) (Boly et al, 2011;Campo et al, 2012;Friston and Penny, 2011;Stephan et al, 2009). In the FFX, the sum of the log-evidence of each subject for each model is calculated to find the optimal model with maximum summed logevidence (Stephan et al, 2009).…”
Section: Model Inversion and Comparisonmentioning
confidence: 99%